Relationship between stress and weight management behaviors during the COVID‐19 pandemic among those enrolled in an internet program. (1st November 2020) - Pellegrini, Christine A.; Webster, Jennifer; Hahn, Korina R.; Leblond, Tiffany L.; Unick, Jessica L.
Abstract: Background: The COVID‐19 pandemic resulted in mandated stay‐at‐home orders, potentially resulting in changes in mental health (e.g., stress, anxiety) and challenges maintaining healthy dietary and physical activity behaviors. Objective: This study examined how stress was associated with mental well‐being and weight loss behaviors during the COVID‐19 pandemic among adults enrolled in an internet‐based weight loss program. Methods: Participants enrolled in a weight‐loss program residing in Rhode Island or Massachusetts, USA, completed a brief survey on their mental health and current weight‐loss behaviors during the COVID‐19 pandemic. Surveys were completed between 14 April 2020 and 21 April 2020, approximately one month after stay‐at‐home orders were mandated. Linear regression was used to examine associations between stress, mental health, and weight‐loss behaviors. Results: A total of 99 participants completed the survey (79% female, 91% white, 52.2 ± 9.8 years, 34.0 ± 5.2 kg/m 2, 77% reported moderate to extreme stress). Greater stress was associated with higher BMI ( p = 0.04), higher education ( p = 0.04), working more hours ( p = 0.003), and having school‐age children at home ( p = 0.002). Greater stress was also associated with higher levels of anxiety, worry, and concern regarding COVID‐19 ( p 's < 0.001) and having less time to spend on weight‐loss efforts ( p < 0.001), after controlling for BMI and education. Conclusions: Many individuals enrolled in a weight‐loss program experienced more stress during COVID‐19 compared to before the pandemic. This stress was related to more mental health challenges as well as more difficulties finding time for weight management efforts.